2016
DOI: 10.1007/978-3-319-45357-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Contexts of Learning

Abstract: This new book series collates key contributions to a fast-developing fi eld of education research. It is an international forum for theoretical and empirical studies exploring new and existing methods of collecting, analyzing, and reporting data from educational measurements and assessments. Covering a high-profi le topic from multiple viewpoints, it aims to foster a broader understanding of fresh developments as innovative software tools and new concepts such as competency models and skills diagnosis continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(13 citation statements)
references
References 430 publications
(556 reference statements)
0
12
0
1
Order By: Relevance
“…To answer this question, we tested the measurement invariance of a two-dimensional model which distinguishes between teacher-guided instruction and unguided inquiry based on Lau and Lam's (2017) study, and compared it to a unidimensional model of inquiry as intended by the PISA questionnaire designers (Müller, Prenzel, Seidel, Schiepe-tiska, & Kjaernsli, 2016).…”
Section: Current Studymentioning
confidence: 99%
“…To answer this question, we tested the measurement invariance of a two-dimensional model which distinguishes between teacher-guided instruction and unguided inquiry based on Lau and Lam's (2017) study, and compared it to a unidimensional model of inquiry as intended by the PISA questionnaire designers (Müller, Prenzel, Seidel, Schiepe-tiska, & Kjaernsli, 2016).…”
Section: Current Studymentioning
confidence: 99%
“…As suggested by the O-P framework, students might be more likely to participate in ICTPAAI when conditions for ICT propensity and opportunity are met (Byrnes & Miller, 2007;Byrnes & Wasik, 2009). Specifically, when students have strong ICT interest (the preference for ICTrelated activities or topics; Goldhammer, Gniewosz, & Zylka, 2016), ICT self-efficacy (the self-perceived ICT competence ;Goldhammer et al, 2016) and ICT autonomy (the perception of independency in ICT activities; Deci & Ryan, 2012;Goldhammer et al, 2016), they are more likely to participate in ICT-related activities. Empirical studies show that educational ICT use is positively related to ICT interest (Areepattamannil & Khine, 2017;Scherer, Rohatgi, & Hatlevik, 2017) and ICT self-efficacy (Areepattamannil & Khine, 2017;Tømte & Hatlevik, 2011).…”
Section: Predictors Of Participation In Ictpaaimentioning
confidence: 99%
“…Autonomy plays an important role in human behaviour (Deci & Ryan, 2012). Experiencing ICT autonomy means students are selfdirected in their use of ICT (Goldhammer et al, 2016). Research has shown that ICT autonomy is positively associated with undergraduates' ICT literacy (Lin & Overbaugh, 2013).…”
Section: Predictors Of Participation In Ictpaaimentioning
confidence: 99%
“…To answer this question, we tested the measurement invariance of a two-dimensional model which distinguishes between teacher-guided instruction and unguided inquiry based on Lau and Lam's (2017) study, and compared it to a unidimensional model of inquiry as intended by the PISA questionnaire designers (Müller, Prenzel, Seidel, Schiepe-tiska, & Kjaernsli, 2016).…”
Section: Current Studymentioning
confidence: 99%